1994
DOI: 10.1089/lps.1994.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pneumoperitoneum: Impact of Body Habitus

Abstract: The purpose of this study was to determine the relationships among pneumoperitoneum pressure, CO2 insufflation volume, and patient height, weight, and body mass index. Forty-one male patients undergoing laparoscopic urologic procedures prospectively had a record made of the delivered volume of CO2 during insufflation to attain intraabdominal pressures of 5, 10, 15, 20, 25, and 30 mm Hg. The relationship of the delivered volume of CO2 insufflated and the intraabdominal pressure was compared statistically to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…It has been observed that the compliance of the abdominal cavity decreases when additional volume is added to the abdominal cavity [37]. This was confirmed clinically by McDougall et al and Abu-Rafea et al who examined 41 and 100 patients respectively during laparoscopy with CO 2 pneumoperitoneum [38,39]. The linear abdominal volume-pressure curve changed to a rather exponential shape when a pressure of 15 mm Hg was achieved by insufflating 3 and 4.5 L of CO 2 in each study (Fig.…”
Section: Iav = κ × [(α/β) × Rc + Ab]mentioning
confidence: 81%
See 2 more Smart Citations
“…It has been observed that the compliance of the abdominal cavity decreases when additional volume is added to the abdominal cavity [37]. This was confirmed clinically by McDougall et al and Abu-Rafea et al who examined 41 and 100 patients respectively during laparoscopy with CO 2 pneumoperitoneum [38,39]. The linear abdominal volume-pressure curve changed to a rather exponential shape when a pressure of 15 mm Hg was achieved by insufflating 3 and 4.5 L of CO 2 in each study (Fig.…”
Section: Iav = κ × [(α/β) × Rc + Ab]mentioning
confidence: 81%
“…The linear abdominal volume-pressure curve changed to a rather exponential shape when a pressure of 15 mm Hg was achieved by insufflating 3 and 4.5 L of CO 2 in each study (Fig. 9, derived from [38,39]). In their studies, the initial abdominal compliance at the beginning of the CO 2 inflation varied between 333 and 400 mL (mm Hg) -1 and at higher IAV (with corresponding IAP above 15 mm Hg) the C ab dropped to 60 and 90 mL (mm Hg) -1 respectively [38,39].…”
Section: Iav = κ × [(α/β) × Rc + Ab]mentioning
confidence: 98%
See 1 more Smart Citation
“…During laparoscopy with limitation of insufflation pressures at 12 to 15 mmHg, the IAV did not reach a critical point at which an exponential increase in IAP occured [13]. As discussed above, the initial phase of the PV curve may indeed be linear (as observed during laparoscopy) but the remaining part is curvilinear or rather exponential [13][14][15]. Because of this exponential relationship, it is important to know both the shape and the position on the curve, as the actual position will determine the corresponding C ab .…”
Section: Abdominal Pressure-volume Relationshipmentioning
confidence: 86%
“…However, it is performed in a restricted space that may limit the surgeon's view and range of motion. Higher CO 2 insufflation pressure provides more insufflation volume [28], and improves surgical field visibility [29], but is associated with increased postoperative side effects [1]. During laparoscopic procedures, maintaining deep NMB, compared to moderate NMB, is associated with improved surgical conditions, as reviewed in [17].…”
Section: Discussionmentioning
confidence: 99%